EFEKTIVITAS METODE PEMBERIAN TUGAS UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN IPADI KELAS 4 MIN 2 SAMBAS TAHUN PELAJARAN 2021/2022 - Nur’Aisyah; Mujahidin; Parni Parni (CV. ADIBA AISHA AMIRA, 2024)
The purpose of this study is to reveal about: 1) Assignment method to be effective in increasing student learning motivation in science learning in grade 4 at MIN 2 Sambas for the 2021/2022 academic year; 2) Implementation steps of the assignment method in science learning in grade 4 at MIN 2 Sambas for the 2021/2022 academic year; 3) Follow up of the assignment method in motivating student in science learning in grade 4 at MIN 2 Sambas for the 2021/2022 academic year. This study used a qualitative approach and a type of descriptive research. Data collection techniques are used the interviews, observation, and documentation. The data analysis techniques used are data collection, data reduction, data display, and conclusions. The results of the study show that: 1) Assignment method to be effective in increasing student learning motivation in science learning in grade 4 at MIN 2 Sambas is: a) Follow the teacher’s instructions in doing the assignment; b) Develop students thinking patterns; c) Train students to be independent; d) Motivate students to do assignment; e) Achieve learning goals. 2) Implementation steps of the assignment method in science learning in grade 4 at MIN 2 Sambas is: a) Provide guidance or supervision in carrying out student assignments; b) Provide encouragement and motivation to students; c) Individual work on assignments by students; d) Explain and provide examples related to the assignment; e) Record the results of the assigned tasks. 3) Follow up of the assignment method in motivating student in science learning in grade 4 at MIN 2 Sambas is: a) Carry out learning evaluation for students; b) Provide assessment to student.